Observation of an exothermic process associated with the in vitro polymerization of brain tubulin. - Berkowitz, S A (1980)
The polymerization of tubulin has been studied with a high-sensitivity differential scanning microcalorimeter, with results which indicate that microtubule assembly can proceed via one or possibly two exothermic reactions. The amount of heat evolution has been found to be far in excess of GTP hydrolysis. The heat liberated has been observed to depend strongly upon the exact experimental conditions, varying from many hundreds of kilocalories per mole of tubulin dimer when dilute tubulin solutions are heated rapidly to a few kilocalories per mole of tubulin dimer when concentrated tubulin solutions are heated slowly. The results are tentatively interpreted in terms of the existence of at least two pathways for the formation of energetically distinct polymers. These findings indicate the importance of kinetic factors in studying tubulin polymerization.